2014
DOI: 10.9790/0853-13445562
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule-1, Vascular Adhesion Molecule- 1, Interlukin1-β, and C - reactive protein Levels in Iraqi Patients with Type 2 Diabetes Mellitus

Abstract: Diabetes mellitus (DM) is considered an inflammatory process with systemic involvement of the vascular tree. Asymptomic coronary artery disease is common in diabetic patients and is a strong predictor for future adverse coronary vascular events as well as early death. The objective of this study was to determine serum levels Intercellular adhesion molecule-1(ICAM-1), Vascular adhesion molecule-1(VCAM-1), interleukin 1-β (IL1-β), and C-Reactive protein (CRP) in relation to some markers indicative of type II dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…Under physiological conditions, IL-1β also play an important role in metabolism of lipids by regulating insulin levels and lipase activity. We also found increased levels of IL-1β and significant association with total cholesterol, LDL and BMI consistent to previous study (Manica-Cattani et al, 2010;Wadood et al, 2014). These results opposed to Li et al study who observed no changes in IL-1β levels in NDD subjects (Li and Shen, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Under physiological conditions, IL-1β also play an important role in metabolism of lipids by regulating insulin levels and lipase activity. We also found increased levels of IL-1β and significant association with total cholesterol, LDL and BMI consistent to previous study (Manica-Cattani et al, 2010;Wadood et al, 2014). These results opposed to Li et al study who observed no changes in IL-1β levels in NDD subjects (Li and Shen, 2019).…”
Section: Discussionsupporting
confidence: 91%